A review on biochar production from different biomass wastes by recent carbonization technologies and its sustainable applications. Issue 1 (February 2022) - Seow, Yee Xuan; Tan, Yie Hua; Mubarak, N.M.; Kansedo, Jibrail; Khalid, Mohammad; Ibrahim, Mohd Lokman; Ghasemi, Mostafa
Abstract: The current environmental pollution and global warming may cause a serious ecological crisis. The conversion of renewable resources, especially from biomass could be a promising option to alleviate this crisis. Traditionally, carbon produced from petrochemicals and coal are typically using large amount of energy and produce substantial quantities of pollutants. There is a need to develop alternative and effective methods to synthesize carbon from renewable resources with high performance and minimal environmental impact. Biochar is a rich carbon material derived from plant-based biomass. Biochar is one of the most ideal materials in various applications by considering it is low thermal conductivity, high porosity, high surface area, renewability, high stability, high carbon content and bulk density. In this regard, biochar has been widely recognized as the suitable candidate for sustainable carbon material. Thus, in this review, recent progresses towards the applications of biochar-based materials in various applications, such as wastewater treatment, soil amendments, catalyst or catalyst precursors and energy storage, are summarized and discussed. The various sources of biomass, synthesis techniques, and the effects of various factors involved in the carbonization process to generate different physicochemical properties biochar from the biomass is elaborated. Also, this review is highlighting the characteristics of the biochar and the carbonization mechanisms of different synthesis technologies. This review shows the great potential of different applications of biochar, which is expected to simulate new development to promote the use of biochar materials to achieve a sustainable environment and circular bio-economy. Graphical Abstract: ga1 Highlights: Discussed the biomass feedstock for biochar materials. The relationship between factors, production technologies and the physicochemical properties of biochar. The synthesis and preparation methods of biochar materials affect their applications. The challenges covered to develop economically feasible biochar production technologies.